A rare case of recurrent paroxysmal supraventricular tachycardia in pregnancy managed with adenosine, a wonder drug - Pakhale, Snehal W.; Gupta, Sadhna D.; Bansal, Anita; Sehra, Angela (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Paroxysmal supraventricular tachycardia (PSVT) is the most common sustained arrhythmia during pregnancy and a challenging situation due to lack of evidence based guidelines. About 50% of PSVT, who fail to respond to vagal maneuvres, responds to therapies as pharmacologic agents as adenosine and electrocardioversion. We reported a case of 29 years old primigravida women with no organic heart disease who presented at 21 weeks of period of gestation with complaints of palpitations and shortness of breath. Her ECG revealed PSVT for which she received adenosine as anti-arrhythmic for conversion to sinus rhythm. She was started prophylactically on tablet metoprolol 25 mg twice daily, as advised by cardiologist. In third trimester, she had recurrent episodes of PSVT for which she received adenosine in emergency department. She delivered a healthy female baby by an elective caesarean section done under spinal anesthesia. Fortunately, her intraoperative and postpartum was uneventful with no recurrence of PSVT during hospital stay. She was discharged on day 4 of caesarean section on tablet metoprolol 12.5 mg twice daily and followed in postpartum period for complications. To summarize, PSVT occurring during pregnancy, labour or at caesarean section is not uncommon. Treatment remains a challenge though, as clinical decision must be tackled with appropriate consideration of both maternal and fetal factors. So, multi-disciplinary approach is needed for treatment including obstetrician, cardiologists, physician and neonatologists. Our case highlighted the necessity of keeping anti-arrhythmic drugs such as adenosine readily available on the labour ward.